Computed tomography value ascites and mesenteric fluid predict intestinal necrosis in strangulated small bowel obstruction - Toshiyuki Suzuki; Akiyo Matsumoto; Daisuke Sugiki; Takahiko Akao; Hiroshi Matsumoto (Scientific Reports)
Abstract The preoperative diagnosis of intestinal necrosis in strangulated small-bowel obstruction (SBO) is clinically important because it is prognostically relevant. The current study assessed the predictors of preoperative intestinal necrosis in strangulated SBO. This retrospective single-center study included 75 consecutive patients undergoing surgery for strangulated SBO. Patients with inguinal, femoral, and obturator hernia were excluded from the analysis. The computed tomography (CT) attenuation value in Hounsfield units (HU) of the strangulated bowel was calculated as the average of the CT attenuation values in HU ​​of the bowel contents measured at three random points. The patients were divided into the intestinal necrosis and without necrosis groups. Clinical and CT scan findings were retrospectively analyzed, and univariate and multivariate analyses were performed. The cutoff CT attenuation value in HU was the mean value. In total, 37 patients presented with intestinal necrosis in the strangulated SBO and 38 did not. In the univariate analysis, strangulated SBO, massive ascites, and mesenteric fluid, which had CT attenuation values ≥ 20 HU, were significant predictors of preoperative bowel necrosis. These factors were also independent predictors of preoperative intestinal necrosis in strangulated SBO in the multivariate analysis. Thus, these factors may help in predicting and managing necrosis in strangulated SBO.